Exploring Healthcare Practitioners’ Knowledge of Rare Diseases in Cameroon - Ngoumou, Rose-Danielle; Bidzogo Ekobono, Louis Marie Gael; Ngoumou , Titus Yannick (International Journal of Innovative Research in Medical Science, 2023)
Rare diseases (RD) are complex medical incidents that constitute a burden for health systems globally. In Cameroon, the absence of a national framework for RDs means that very little is known about these diseases. Many health professionals due to the rarity of cases and complexity of symptoms, face challenges in detecting and treating them. The aim of this paper is to examine the knowledge of Cameroonian physicians on RDs in order to highlight the medical constructions of RDs in Cameroon. The study is cross-sectional and associates quantitative and qualitative research approaches with 23 health practitioners who responded to an open-ended questionnaire to (1) evaluate their knowledge of RDs, (2) describe the medical discourse on RDs in Cameroon and (3) identify prevailing RDs in Cameroon. The study showed on the one hand that, health professionals have strong theoretical knowledge of RDs. About 40.9% know that an RD is one that has a very low prevalence. 73.1% have come across a case of RD in their practice. RDs practitioners indicated they have encountered in their practice were mainly Down syndrome, hemophilia, and G6PD. 81% say they have difficulties detecting an RD. On the other hand, there are certain health practitioners who view that RDs are not (yet) a public health concern in Cameroon when there is a rise of non-communicable diseases like high blood pressure, diabetes, etc. Treatment strategies highlighted were mainly multidisciplinary consults, surgery, and specialized care. The study suggests that decision makers and practitioners should design strategies to strengthen expertise for the diagnostic and management of RDs in Cameroon. Also, health practitioners should be trained regularly on how to manage RDs.